Pendapatan dan Pengaruh Belanja Modal terhadap Investasi Swasta Diindonesia dengan Pertumbuhan Ekonomi Sebagai Variabel Intervening - Awaliyah Matondang, Khairani; Meutia Fahrani; Deyren Firmansyah; Ulina Br Naibaho, Novianti Naomi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Private investment is one of the important factors that can boost economic growth. Government capital expenditure can also play a role in increasing private investment. This study aims to analyze the effect of capital expenditure on private investment in Indonesia with economic growth as an intervening variable. The research data was obtained from 2010-2019 secondary data sourced from the Central Statistics Agency (BPS) and the Ministry of Finance of the Republic of Indonesia. The research data were analyzed using multiple regression analysis method with intervention variables. The results showed that capital expenditure had a positive and significant effect on economic growth. Economic growth also has a positive and significant effect on private investment. Capital expenditure indirectly has a positive and significant effect on private investment through economic growth variables. Based on the results of the study, it can be concluded that capital expenditure can encourage private investment through increased economic growth. Therefore, the government needs to increase capital expenditure to boost economic growth and private investment.